Evaluation of flowering and fruiting in a number of modern tomato hybrids being introduced to protected cultivation - سمرة, بديع محمد; إبراهيم, نور باسم (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out in the village of Bustan Al-Basha in the Jableh in coastal region within a research station of the Sulaiman Agricultural Corporation at an altitude of 10 meters above sea level. The research was carried out during the 2019-2020 agricultural season in plastic green house. The plant material used in the study is 5 new hybrids of selected and genetically improved tomatoes, indeterminate, in addition to the hybrid pestona (control). All the studied hybrids were grafted on the original (Defenser),the two stems were raised. The experiment contain 6 treatments and three replicates for each treatment, at a rate of (10) plants per replicate, with design of complete random sectors. The aim of the research is to compare these hybrids and test the degree of success of their cultivation The results showed that the hybrid (1905, 1904) was significantly superior in the number of flower clusters formed on the plant over the rest of the hybrids, and the hybrid (1909-1905) significantly outperformed the internodes in the superiority of the hybrid 1905, 1909) in earlier production than the rest of the hybrids, and the fruits of all strains took the flat spherical shape and the hybrid 1905 its fruits took a spherical shape.